Konsep Pendidikan Humanistik Ki Hadjar Dewantara - Basuki, Basuki (Universitas Mathla'ul Anwar Banten, 2025)
Humanistic education, according to Ki Hadjar Dewantara, is an educational concept that aims to shape students into individuals who are spiritually and physically independent, while viewing humans as holistic beings. This study seeks to describe Ki Hadjar Dewantara’s formulation of humanistic education through a literature review method, using his own works on education as primary sources, alongside relevant supporting literature. The findings reveal that Ki Hadjar Dewantara’s concept of humanistic education is grounded in several key principles: (1) viewing humans as noble beings endowed with the unity of thought, feeling, and will—known as the soul’s trilogy of cipta, rasa, and karsa—which distinguishes humans from animals; (2) the teacher functions as a role model and a moral guide, particularly in the realms of faith and religion, and engages with students through the ethical principles of Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani; (3) students are treated as learning subjects who inherently possess potential from birth and are responsible for their own education; (4) the ultimate goal of education is to produce independent individuals; and (5) the educational method employed is the Among method.